Effects of long-term administration of Multi-Strain Probiotic on circulating levels of BDNF, NGF, IL-6 and mental health in patients with multiple sclerosis: a randomized, double-blind, placebo-controlled trial. (1st February 2022) - Rahimlou, Mehran; Hosseini, Seyed Ahmad; Majdinasab, Nastaran; Haghighizadeh, Mohammad Hosein; Husain, Durdana
ABSTRACT: Background: Mental disorders is one of the main causes of disability and lower life expectancy among patients with Multiple Sclerosis (MS). The present trial aimed to examine the efficacy of multi-strain probiotic supplementation on circulating levels of BDNF, NGF, IL-6 and mental health in patients with MS. Methods: This trial was conducted among 70 patients with MS that referred to the MS Association. Patients were randomized into intervention and control groups to receive 2 multi-strain probiotic capsules or placebo, daily for six months. Serum BDNF, NGF and IL-6 was measured by ELISA kits. Mental health parameters were assessed by valid questionnaires in the baseline and end of the study. Results: Of the 70 patients enrolled in this study, 65 subjects were included in the final analysis. From baseline to 6 months, probiotic supplementation resulted in a significant increase in BDNF and a significant reduction in the IL-6 levels ( P  < 0.001). Our findings revealed that probiotic supplementation compared to placebo caused a significant improvement in the general health questionnaire-28 (GHQ-28) (−5.31 ± 4.62 vs. −1.81 ± 4.23; P  = 0.002), Beck Depression Inventory-II (BDI-II) (−4.81 ± 0.79 vs. −1.90 ± 0.96; P  = 0.001), Fatigue Severity Scale (FSS) (−3.81 ± 6.56 vs. 0.24 ± 5.44; P  = 0.007) and Pain Rating Index (PRI) (−3.15 ± 4.51 vs. −0.09 ± 3.67; P  = 0.004). However, we not found any significant difference between the two groups in other factors ( P  > 0.05). Conclusion: Overall, six months of probiotic supplementation resulted in greater improvement in mental health parameters.